Spatial distribution and effective depth of roots of camu-camu with and without mulch - Abanto-Rodríguez, Carlos (2023)
In South America, o camu-camu has been domesticated, however, for its cultivation there is still little technical information to guarantee its adaptability and productivity in places with a well-defined dry season. The objective of this study was to characterize the spatial distribution of the root system and determine the effective depth (EP) of roots in camu-camu plants with and without mulch (WM) in uplands conditions. In an orchard, 3 plants with 3, 5 and 7 years each were chosen at random. Then mulch composed of grass (Trachypogon plumosus) was placed on a plant of each age in the canopy projection. After 12 months, the volume and EP of the roots in the 3-year-old plants with mulch was 200 mm3 and 0.3 m, and without mulch it was 500 mm3 and 0.48 m, respectively. In 5-year-old plants it was 4000 mm3 and 0.43 m with mulch, and without mulch it was 6000 mm3 and 0.64 m; and in plants with 7 years old, the volume and PE of the roots with mulch were 12000 mm3 and 0.58 m, and without mulch of 10000 mm3 and 0.71 m, respectively. The effective depth equivalent to 80% of the root concentration was lower with the use of dead vegetation cover, which is very important for the camu-camu crop, as it allows the application of a more precise and efficient water layer through irrigation.